2009
DOI: 10.1007/s11104-009-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Elymus natans improves soil quality of a heavily degraded alpine meadow in Qinghai-Tibetan Plateau, China

Abstract: Elymus natans is a dominant native species widely planted to restore the heavily degraded alpine meadows in Qinghai-Tibetan plateau. The objective of this study was to determine how E. natans establishment affected the quality and fertility of a heavily degraded soil. Soil samples (at depths of 0-10, 10-20 and 20-30 cm) were collected from the 3-and 7-year-old E. natans re-vegetated grasslands, and in the heavily degraded alpine meadow (control). The establishment of E. natans promoted plant cover and abovegro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
65
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 15 publications
5
65
0
1
Order By: Relevance
“…However, the grassland systems in this region have suffered from severe degradation driven by a range of factors including climate change, overgrazing, overcultivation and poor management (Han et al, 2008;Li et al, 2009;Wu et al, 2009Wu et al, , 2010Feng et al, 2010), and the degraded land area has been increasing at 1.2-7.44 % per year (Ma et al, 2007). Since the 1990s, the restoration of degraded grasslands has attracted considerable attention (Kang et al, 2007;Han et al, 2008), and some efforts have recently been directed towards grassland restoration and maintenance by increasing aboveground plant abundance (Niu et al, 2009) and biodiversity (Wu et al, 2009;Niu et al, 2010) and improving soil organic matter content and nutrient availability (Cao et al, 2004;Wu et al, 2010;Sun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the grassland systems in this region have suffered from severe degradation driven by a range of factors including climate change, overgrazing, overcultivation and poor management (Han et al, 2008;Li et al, 2009;Wu et al, 2009Wu et al, , 2010Feng et al, 2010), and the degraded land area has been increasing at 1.2-7.44 % per year (Ma et al, 2007). Since the 1990s, the restoration of degraded grasslands has attracted considerable attention (Kang et al, 2007;Han et al, 2008), and some efforts have recently been directed towards grassland restoration and maintenance by increasing aboveground plant abundance (Niu et al, 2009) and biodiversity (Wu et al, 2009;Niu et al, 2010) and improving soil organic matter content and nutrient availability (Cao et al, 2004;Wu et al, 2010;Sun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that heavily and severely degraded grassland (called the "black beach") represented approximately 34 and 8 %, respectively, of the grassland area in the headwaters region (Ma et al 2006;Shang et al 2008;Wang et al 2009). Despite numerous efforts to protect the grassland resource in this area, grassland degradation is continuing due to overgrazing, overexploitation of medicinal plants, destruction by rodents, and climatic warming and drought (Zhou et al 2005;Wang and Fu 2004;Gao et al 2009;Feng et al 2010;Wang et al 2008Wang et al , 2011bLi et al 2011a, b;Xu et al 2012). Declines in ecosystem services with grassland degradation may be attributed to changes in ecosystem composition (Shang et al 2008;Wang et al 2009), the loss of biodiversity (Harris 2010;Dong et al 2010), the decline of ecosystem productivity, and the decline of soil fertility (Shang et al 2008;Wang et al 2009Wang et al , 2011a.…”
Section: Introductionmentioning
confidence: 99%
“…However, overgrazing is one of main causes of grassland desertification (Deng et al 2014a;Su et al 2005;Wu et al 2009), including desertification of soil properties (chemical and physical) and negative effects of vegetation, including reduction in biomass, vegetation coverage, and species diversity and increase in undesirable vegetation (Deng et al 2014a;Zhu et al 2016). Grazing prohibition (exclusion) or fencing is the common grassland management to reverse desertification grassland throughout the world in recent decades (Deng et al 2014b;Deng et al 2014a;Ma et al 2015;Wu et al 2009), andFeng et al (2010) founded that Elymus natans establishment is an effective and applicable measure in restoring heavily degraded alpine meadow in the region of the Qinghai-Tibetan Plateau through 3-and 7-year-old E. natans re-vegetated grasslands.…”
mentioning
confidence: 99%
“…In terms of vegetation recovery and soil property improvement for the alpine meadow, livestock exclusion or fencing rather than grazing was found to be beneficial, which changes the biomass and soil properties to the better (Shi et al 2010;Ma et al 2015;Wu et al 2009). The lightly and moderately degraded alpine meadow was found to recover by being kept away from disturbance, whereas the heavily and extremely heavily degraded alpine meadow requires artificial and semi-artificial grassland establishment for ecosystem restoration (Dong et al 2013;Feng et al 2010).…”
mentioning
confidence: 99%